An equicorrelation-based multiuser communication scheme for DS-CDMA systems. - Weihua Ye (IEEE Transactions on communications)
An equicorrelation-based multiuser communication (ECBMC) scheme for direct-sequence code-division multiple-access (DS-CDMA) systems is presented. The ECBMC receiver has low computational complexity that is comparable to that of the conventional detector. By using the equality of cross correlations, the ECBMC scheme can completely eliminate multiple-access interference (MAI) in a synchronous single-path DS-CDMA network. The system performance is independent of the number of active users. The scheme is extended to include the effects of multipath fading. It is able to suppress a major portion of the MAI. This proposed ECBMC scheme is quite attractive for an MAI-dominant environment.